Oman's transformation after 1970 - Peterson, John 1947- (Brill, 2024)
"Oman's 1970 coup launched a new political and economic structure that was created by and for Sultan Qaboos. The initially haphazard construction matured into a durable structure that continues under Sultan Haitham. This work details the early construction of the Qabusid state in the 1970s-1980s, emphasizing the interplay between personalities and the process of institutionalization. The narrative continues to the present demonstrating the resilience of the Qaboosid system"--
Keywords: Qabus bin Said / Sultan of Oman / 1940-2020 / Influence; Oman / Economic conditions / 20th century; Oman / Politics and government / 1970-2020; Oman / Politics and government / 21st century